THE EDUCATION LEADERSHIP IN GLOBAL PERSPECTIVE - Yuswo Adifatoni (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
This article looks closely on the deep identification of the global theoretical perspectives in educational leadership and Javanese culture leadership as the main sources of Indonesian leadership models. The discussion focuses on the definition of leadership, various leadership styles, leadership approaches, concept of power, as well as the issue of gender and leadership. At the end of discussion will give understanding on the quality of school principal leadership not only theoretical ideas but also the practical one for the Indonesian school